(untitled) (African Journal of Public Administration & Management, 2026)
Citizens globally expect faster, transparent, and convenient services. The Ministry of Housing and Urban Development is digitizing two ncritical processes: Land Disposal (Sale of Land) Building Permit Application and Approval Current systems are fully manual, slow, and inefficient, limiting the GIYH vision